Ameliorative activity of ethanolic flower extract of Nyctanthes arbor-tristis (L.) against scopolamine-induced amnestic effect and profiling of active compounds using gas chromatography-Mass spectrometry and ultra-performance liquid chromatography-quadrupole-time-of-flight mass spectrometry - Mishra A.K.; Upadhyay P.; Dixit J.; Kumar P.; Tiwari K.N.; Mishra S.K.; More R.; Singh J. (My University, 2025)
Background: Amnesia state damages the hippocampus and leads to the loss of short-term memory. Nyctanthes arbor-tristis (L.) is used in traditional medicines to treat various ailments. Objective: In the present investigation, we evaluated the efficacy of ethanolic extract of flowers of N. arbor-tristis against scopolamine-induced amnestic effect in male Wister rats and intended to identify the major compounds present in the extract. Materials and Methods: The anti-amnestic profile of flower extract was screened by elevated plus maze (EPM), passive avoidance (PA), and Morris water maze (MWM) tests. Results: EPM test confirmed the anxiolytic effect of the extract in rats and decreased the transfer latency in the protected arm of the EPM. During PA test, the extract resulted significant increase in step-down latencies during both the acquisition and retention sessions. In MWM task, the scopolamine injection significantly prolonged the escape latency time, whereas this time was shortened in flower extract-treated group. For the confirmation of anti-amnestic effect of extract, acetylcholine (Ach) content, acetylcholinesterase (AChE) activity, superoxide dismutase (SOD), reduced glutathione (GSH), and malondialdehyde (MDA) levels in hippocampus brain were evaluated. The extract significantly increased ACh content and decreased the activity of AChE in the hippocampus of the brain. Similarly, the extract declined the MDA and increased the GSH and SOD levels in brain tissues. The phytol (RT 19.69) and loliolide (RT 23.50) were identified in the extract through gas chromatography-mass spectrometry analysis. The four major compounds such as 4-coumaric acid, chlorogenic acid hemihydrate, chalcone, and melatonin were identified using ultra-performance liquid chromatography-quadrupole-time-of-flight mass spectrometry. Conclusion: The anti-amnestic effect of ethanolic extract of the flower was confirmed. It contains several compounds which might be useful in the treatment and to control several neurodegenerative diseases. © 2019 Pharmacognosy Magazine Published by Wolters Kluwer - Medknow.